Nursing research using ethnography : qualitative designs and methods in nursing - De Chesnay, Mary (Qualitative designs and methods in nursing., 2014)
Ethnography is a qualitative research design that focuses on the study of people to explore cultural phenomena. This concise, "how to" guide to conducting qualitative ethnography research spearheads a new series, Qualitative Designs and Methods, for novice researchers and specialists alike focusing on state-of-the-art methodologies from a nursing perspective. Scholars of qualitative ethnography research review the philosophical basis for choosing ethnography as a research tool and describe in depth its key features and development level. They provide directives on how to solve practical problems related to ethnography research, nursing examples, and discussion of the current state of the art. This includes a comprehensive plan for conducting studies and a discussion of appropriate measures, ethical considerations, and potential problems. Examples of published ethnography nursing research worldwide, along with author commentary, support the new researcher in making decisions and facing challenges. Each chapter includes objectives, competencies, review questions, critical thinking exercises, and web links for more in-depth research. A practical point of view pervades the book, which is geared to help novice researchers and specialists expand their competencies, engage graduate teachers and students and in-service educators and students, and aid nursing research in larger health institutions. Key Features: Includes examples of state-of-the-art ethnography nursing research with content analysis ; Presents a comprehensive plan for conducting studies and appropriate measures, ethical considerations, and potential challenges ; Describes theoretical underpinnings, key features, and development level ; Written by ethnography scholars from around the world.